Humic Acid Alleviates Fe Chlorosis in Graminaceous Plants Through Coordinated Fe-Dependent and Fe-Independent Mechanisms - Garnica, Maria; Baigorri, Roberto; San Francisco, Sara; Zamarreño, Angel M.; Garcia-Mina, Jose M. (Frontiers in Plant Science, 2022)
Many studies have shown the close relationship between the beneficial action of soil and sedimentary humic acids on the growth of plants cultivated in calcareous soils and their ability to improve Fe plant nutrition. These results have been ascribed to the humic acid capability to improve Fe solubility and bioavailability. However, other effects more related to a humic acid action on the specific mechanisms activated in roots of plants under Fe deficiency cannot be ruled out. Although this question has been studied in dicotyledonous plants, in graminaceous plant there are no specific studies. Here we investigate whether the ability of a humic acid extracted from peat (HA) to improve Fe nutrition in wheat is linked to specific actions on Fe availability within the plant and the release of phytosiderophores from the root to the nutrient solution. The results show that HA can improve the physiological status of Fe deficient wheat plants by alleviating some of the deleterious consequences of Fe deficiency on plant development. This action of HA is associated with increases in the Fe-active pool in leaves as well as the plant ability to release phytosiderophores from the root to the rhizosphere. This effect may involve a signaling role of tZR and cZR, since the concentration of these phytohormones was enhanced by HA in Fe deficient plants. All these actions are ascribed to HA in itself and not to the Fe provided by HA structural composition.